2017
DOI: 10.1007/978-3-319-58524-6_26
|View full text |Cite
|
Sign up to set email alerts
|

A New Information Theory-Based Serendipitous Algorithm Design

Abstract: The development of information technology has stimulated an increasing number of researchers to investigate how to provide serendipitous experience to users in the digital environment, especially in the fields of information research and recommendation systems. Although a number of achievements have been made in understanding the nature of serendipity in the context of information research, few of these achievements have been employed in the design of information systems. This paper proposes a new serendipitou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…More recently, previous research has highlighted how making connections is an important point for serendipitous engineering [13]. Based on previous research outcome from Information Research, an Information Theory-based algorithm has been proposed to better understand serendipity in the Recommender System [36]. Furthermore, a systematic context-based study among Chinese Scholars has been conducted and proves the effectiveness of the proposed algorithm [35].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…More recently, previous research has highlighted how making connections is an important point for serendipitous engineering [13]. Based on previous research outcome from Information Research, an Information Theory-based algorithm has been proposed to better understand serendipity in the Recommender System [36]. Furthermore, a systematic context-based study among Chinese Scholars has been conducted and proves the effectiveness of the proposed algorithm [35].…”
Section: Introductionmentioning
confidence: 94%
“…The understanding of serendipity, as a user-centered concept, has been a gap for a while. Until recently, an awareness of this gap has led a conceptual bridge, which introduced serendipity from Information Research into Recommender Systems, by proposing an Information Theory-based algorithm [36]. To further investigate this algorithm, it needs to be implemented as an end-to-end recommender system, but it is difficult to do so.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the theoretical support of CHESTNUT [24], its effectiveness [23] and practical system performance [16] has been examined earlier, the missing validation from real-world users is still missing. Also, a large-scale user study would also help to uncover several issues, which are not capable to be found through off-line evaluations, and enhance its practicality.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Towards a more comprehensive understanding of serendipity, we have built CHESTNUT , the first serendipitous movie recommender system with an Information Theory-based algorithm, to embed a more comprehensive understanding of serendipity in a practical recommender system [16,24]. Although experimental studies on static data sets have shown that CHESTNUT could achieve significant improvements (i.e.…”
Section: Introductionmentioning
confidence: 99%